Empreendedorismo em cena : associações entre narrativas audiovisuais e competências do empreendedor em ambientes educacionais - Santos, Glauco Henrique Cruz (2021)
The teaching of entrepreneurship is growing throughout the country, considering Global research, such as the Global Entrepreneurship Monitor (GEM) and National ones, such as SEBRAE. Before and mainly during the COVID-19 pandemic, there was an acceleration in the demand of higher education students for this subject, taking into account the transversal teaching that adds its use to other areas of education. Seeking practical ways of working the themes in educational environments, whether distance learning or in the classroom, this study chose to explore and analyze two aspects: the use of audiovisual narratives as a pedagogical tool and the choice for Entrepreneurial Skills as an object of study. Thus, the research aims to understand how associations between audio-visual narratives and Entrepreneur skills can contribute to the teaching and learning of an Entrepreneurship discipline. Based on an intentional and intuitive selection, five audiovisual products were selected with varied genres and that have entrepreneurship in an objective and/or subjective way. The analyzes were carried out using resources such as analogies, metaphors and allusions, in order to create associations between the audiovisual narrative of each product and the Entrepreneurial Competences studied. Based on criteria for both the application and the development of these analyses, each of the narratives was detailed, including a suggestion for use in educational environments. A teaching plan was drawn up to suggest the use of one of these products in these environments. It is concluded that the use of the cinema tool, based on the model applied in this study and with the creativity of teachers to search for new narratives, can contribute to a differentiated teaching solution, reducing resistance to the tool, both for on the part of teachers and students and valuing the vision of the future, the difficulties imposed by the last two generations, Z and Alpha, which today form the foundation not only of education, but of the course of society. Given this reality, it is believed that it is necessary to launch a new look at education/teaching/learning, through methodological revisions that can coopt students, capturing their attention, inducing their reflections and, mainly, contributing to an experiential learning favorable to their mental, social and professional development.